Shifts and patterns in Maltese - Puech, G. (Gilbert); Saade, Benjamin (Studia typologica ;, 2016)
As an Arabic language with a heavily mixed Semitic-Romance-English lexicon, Maltese serves as a laboratory for linguistic research on questions of variation, typological classification, bilingualism, and language contact. In this book, studies on phonological, morphological, and syntactic variation are complemented by investigations on bilingual practices on Malta, aspects of language technology, and language contact.